Parasitoid interactions in behavioral ecology and biological control - Batchelor, Timothy Peter (2005)
This thesis presents laboratory investigations on the competitive interactions which take place within and between bethylid parasitoids. Part one investigates the compatibility of three bethylids (Cephalonomia hyalinipennis, Cephalononlia stephanoderis and Prorops nasuta) for biocontrol releases against the principal pest of coffee, the coffee berry borer (CBB), Hypothenemus hampei. Cephalonomia hyalinipennis is able to hyperparasitise and consume pupae of C stephanoderis and P. nasuta. Cephalonomia stephanoderis also engages in intra-guild predation, consuming pupae of C hyalinipennis. In contests for CBB hosts, fatal fighting occurs in 69% of inter-specific replicates but never occurs in intra-specific replicates. This suggests that interspecific competition is stronger than intraspecific competition and that species coexistence may be compromised. Cephalonomia tephanoderis is the superior interspecific contestant while P. nasuta is the least successful and never kills an opponent. Where CBB infested coffee berries are provided to the three bethylids, coexistence between species is possible, but rare, within a single coffee berry. Prorops nasuta is the most successful species in interspecific replicates and replicates containing C. hyalinipennis generally have low production, regardless of the species combination added. Part two investigates contest interactions, the variables that influence contest outcome between Goniozus nephantidis females and chemical release. Prior ownership and difference in contestant weight have positive influences on contest outcome. Host weight positively influences the outcome of contests between two 'owners' and 'intruder' take-over success increases when intruders are older than owners. Seven bethylid species are found to release volatile chemicals when stressed. A pilot study identifies the volatile chemical in G. nephantidis and employs Atmospheric Pressure Chemical Ionisation-Mass Spectrometry for real-time analysis of chemical release during contest interactions. The appendix contains an advanced investigation using this technique. Bethylids are useful model organisms for the study of competitive interactions but appear to be generally ineffective as biological control agents.